Penyelesaian Sengketa Wanprestasi Jual Beli Online Pada Pembayaran Metode Cash On Delivery (COD) Di Marketplace Shopee - Alya Para Mestri; Arief Suryono (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
This research analyzes the types of dispute resolution that can be carried out due to acts of default committed by buyers in online buying and selling using the Cash On Delivery (COD) payment method in the Shopee marketplace. This research is normative legal research that is prescriptive and applied. The collection of legal materials is through library research, including primary and secondary legal materials. This research aims to find out and examine what dispute resolution can be carried out by sellers due to acts of default committed by buyers in online buying and selling using the COD payment method on the Shopee marketplace in terms of statutory regulations and Shopee's Terms of Service.